JAK inhibition alleviates the cellular senescence-associated secretory phenotype and frailty in old age - Xu, Ming; Tchkonia, Tamara; Ding, Husheng; Ogrodnik, Mikolaj; Lubbers, Ellen R; Pirtskhalava, Tamar; White, Thomas A; Johnson, Kurt O; Stout, Michael B; Mezera, Vojtech; Giorgadze, Nino; Jensen, Michael D; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
Chronic, low grade, sterile inflammation frequently accompanies aging and age-related diseases. Cellular senescence is associated with the production of proinflammatory chemokines, cytokines, and extracellular matrix (ECM) remodeling proteases, which comprise the senescence-associated secretory phenotype (SASP). We found a higher burden of senescent cells in adipose tissue with aging. Senescent human primary preadipocytes as well as human umbilical vein endothelial cells (HUVECs) developed a SASP that could be suppressed by targeting the JAK pathway using RNAi or JAK inhibitors. Conditioned medium (CM) from senescent human preadipocytes induced macrophage migration in vitro and inflammation in healthy adipose tissue and preadipocytes. When the senescent cells from which CM was derived had been treated with JAK inhibitors, the resulting CM was much less proinflammatory. The administration of JAK inhibitor to aged mice for 10 wk alleviated both adipose tissue and systemic inflammation and enhanced physical function. Our findings are consistent with a possible contribution of senescent cells and the SASP to age-related inflammation and frailty. We speculate that SASP inhibition by JAK inhibitors may contribute to alleviating frailty. Targeting the JAK pathway holds promise for treating age-related dysfunction.